Learning Strategy of Social Studies Based on Cultural Literacy in Forming Local Wisdom Characters at SDN 2 Tanggunggunung Tulungagung Regency - Widodo, Dadang Puji; Rindrayani , Sulastri Rini; Ana, Ria Fajrin Rizqy (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
The strategy in learning for students must be right, we need an approach so that we can know each child's character. Learning strategies make it easier for students to receive or understand learning materials, and ultimately learning objectives can be mastered by students. The purpose of this study was to determine the techniques and implementation of cultural literacy-based learning, identify social studies learning media based on cultural literacy and analyze the evaluation of student learning outcomes after cultural literacy-based social studies learning. The research method used is a qualitative method. The source of research data comes from primary and secondary data sources. Data collection techniques through interview methods, document studies, observations. The validity test of research data uses source triangulation techniques. Data analysis uses analysis, namely data reduction, data presentation and drawing conclusions. The results of the study The cultural literacy-based social studies learning technique used by teachers at SDN 2 Tanggunggunung uses lecture techniques and discussion techniques. Cultural literacy learning in the classroom is intended to make students more active, creative, critical and have literacy skills. The media teachers use in cultural literacy-based learning is using ebooks, internet media, and observing conditions in the Tulungagung Regency community, and in our environment. Written assessments are used to determine the extent of students' cognitive abilities, while non-written assessments are used to determine students' affective abilities, especially their ability to recognize cultural literacy.